2017
DOI: 10.5483/bmbrep.2017.50.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Impaired phagocytosis of apoptotic cells causes accumulation of bone marrow-derived macrophages in aged mice

Abstract: Accumulation of tissue macrophages is a significant characteristic of disease-associated chronic inflammation, and facilitates the progression of disease pathology. However, the functional roles of these bone marrow-derived macrophages (BMDMs) in aging are unclear. Here, we identified age-dependent macrophage accumulation in the bone marrow, showing that aging significantly increases the number of M1 macrophages and impairs polarization of BMDMs. We found that age-related dysregulation of BMDMs is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…The local microenvironment plays a critical role in shaping what genes are expressed [17], and macrophages can display both M1 and M2 markers in vivo and are not necessarily exclusively pro-inflammatory or antiinflammatory [15]. For instance, there is evidence that M2-like macrophages can be pro-inflammatory [18], and that a pro-inflammatory M2 phenotype seems to accumulate in some, but not all, tissues with age [19][20][21][22][23][24]. M2 phenotypes have recently been divided into M2a, M2b, M2c, and other subdivisions by some authors based off the stimuli used to polarize them in vitro [15].…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…The local microenvironment plays a critical role in shaping what genes are expressed [17], and macrophages can display both M1 and M2 markers in vivo and are not necessarily exclusively pro-inflammatory or antiinflammatory [15]. For instance, there is evidence that M2-like macrophages can be pro-inflammatory [18], and that a pro-inflammatory M2 phenotype seems to accumulate in some, but not all, tissues with age [19][20][21][22][23][24]. M2 phenotypes have recently been divided into M2a, M2b, M2c, and other subdivisions by some authors based off the stimuli used to polarize them in vitro [15].…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…Phytate possesses six phosphate groups with strong negative charges at physiological pH, which suggests that phytate cannot cross the lipid bilayer of the plasma membrane without a specific receptor (Ozaki et al, 2000). In support of this possibility, we found that phytate is only engulfed by hepatic Kupffer cells and tissue macrophages in vivo when we intravenously injected iron-containing phytate particles into live mice (Kim et al, 2017; Lee et al, 2018), indicating that phytate cannot penetrate membranes of epithelial cells in the intestine. Together, these findings suggest that phytate is not absorbed in the intestine and that only products generated through the hydrolysis of phytate, phosphate, or myo -inositol can be absorbed in the intestine of rats fed phytate-containing low-Ca 2+ diets.…”
Section: Discussionmentioning
confidence: 71%
“…Antigen retrieval for IHC was performed in Tris/EDTA (pH 9.0) for 2–3 min. IHC was performed with the following polyclonal antibodies (Santa Cruz) at 25°C for 2 h: CYP27B1 (M-100, 1:50), CYP24A1 (S 20, 1:50), VDR (D-6, 1:50), RANKL (N-19, 1:50), or osteoprotegerin (N-20, 1:50), as described previously (Kang et al, 2017). Horseradish peroxidase-conjugated secondary antibodies were detected with 3,3,-diamino-benzidine tetrahydrochloride substrate (Dako, Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Elevated mTOR signaling causes microglia to adopt a noninflammatory reactive phenotype and to promote the proliferation of astrocytes 35 . Additionally, bone marrow-derived macrophages (BMDMs) that had phagocytosed apoptotic cells showed decreased production of interleukin-6 (IL-6) after lipopolysaccharide stimulation 46 , 47 . LSECtin promotes apoptotic cell clearance by macrophages and induces intestinal regeneration and maintenance of the mucosal barrier after injury 12 .…”
Section: Resultsmentioning
confidence: 99%